Servicification of Manufacturing and Boosting Productivity through Services Sector Reform in Turkey - Haven, Thomas; Van Der Marel, Erik (World Bank, Washington, DC, 2018)
There is a global trend toward more production, use, and sale of services by manufacturing firms. This phenomenon is known as the servicification of manufacturing. Services inputs as well as services activities within manufacturing firms account for over half of the value of manufacturing exports. This paper uses a unique firm-level data set to analyze the link between servicification and productivity in Turkey. Although servicification has the potential to boost firm performance, the opposite appears to be the case in Turkey: manufacturing firms with service affiliates tend to be less productive. The type of services produced matters. For instance, firms that have post-manufacturing (transport and distribution) service affiliates are particularly less productive. Regulatory restrictions in services are explored as an explanatory factor. Productivity gaps appear in the same areas where services are more restricted, such as in post-manufacturing services.